Ethnography of the Local Wisdom of Mutual Cooperation (Gotong Royong) and Collective Contributions (Patungan) in the Construction of Nurul Nisa Ulima Indah Mosque, Batu Merah Village, Ambon: An Islamic Perspective - Ismail Borut; Nurfadila Hasani; Halima Bugis; Andi Sitti Marwah (IAIN Ambon, 2026)
This research employs a qualitative approach within an ethnographic framework to analyze the behavioral patterns, social interactions, and value systems of the multicultural community in Maluku, specifically the residents of RT 06/RW 17 Ulima Indah, Negeri Batu Merah, Ambon, regarding their practices of gotong royong (mutual cooperation) and patungan (communal funding) in the construction of Masjid Nurul Nisa. The study examines local wisdom in mutual cooperation, such as Malehar, Hiwait/Fitwait, Yomaalai Bamtusaoo, Masohi, Marhen, and Poompu Ompu, as well as communal funding traditions including Amban Mirim, Hiwait/Fitwait, Jiwaha, and Yalim. This research finds that these local wisdom traditions contain values that are fundamentally aligned with Islamic principles, particularly ta'awun (mutual cooperation), ukhuwah (brotherhood), and infaq/sadaqah (charitable contribution). The integration of local cultural practices with Islamic values has strengthened the social cohesion of the multicultural community and facilitated the successful construction and development of the mosque.